2020
DOI: 10.1177/8755293020919416
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of spectral acceleration values of vertical and horizontal ground motion pairs

Abstract: We present correlation coefficient estimates between a number of ground motion intensity measures ( IMs), as measured from the NGA-West2 database, with focus on the correlation of vertical–vertical and vertical–horizontal ground motion components. The IMs considered include spectral accelerations with periods from 0.01 to 10 s, peak ground acceleration, peak ground velocity, and significant duration (for 5%–75% and 5%–95% definitions). To facilitate their use, parametric equations are also fitted to the correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 42 publications
6
17
0
Order By: Relevance
“…Using a subset of the NGA-West2 database, Baker and Bradley (2017) showed that there is no apparent systematic dependence on M w , R rup , and V s 30 9 for the correlation of SA ordinates with themselves and with D s575 . Similar remarks were made by Kohrangi et al (2020) regarding the vertical and horizontal ground-motion IMs. Wang and Du (2012) also concluded no dependence of CAV-SA correlation on M w and site condition; however, they showed its dependence on distance and categorization of ground motions as pulse-like motions using the NGA-West1 subset and GMMs.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Using a subset of the NGA-West2 database, Baker and Bradley (2017) showed that there is no apparent systematic dependence on M w , R rup , and V s 30 9 for the correlation of SA ordinates with themselves and with D s575 . Similar remarks were made by Kohrangi et al (2020) regarding the vertical and horizontal ground-motion IMs. Wang and Du (2012) also concluded no dependence of CAV-SA correlation on M w and site condition; however, they showed its dependence on distance and categorization of ground motions as pulse-like motions using the NGA-West1 subset and GMMs.…”
Section: Resultssupporting
confidence: 73%
“…Conventionally, pseudo-spectral accelerations (SAs) are used to represent the target probabilistic and scenario-based seismic hazards for the purpose of ground-motion selection. The dependence of correlation coefficients on the ground-motion causal parameters, that is, rupture magnitude, distance, and site condition, does not seem substantial (Baker and Bradley, 2017; Kohrangi et al, 2020; Kotha et al, 2017; Wang and Du, 2012). The dependence of correlation coefficients on adopted ground-motion models (GMMs) and their corresponding between-event residuals is also reported to be not significant (Baker and Jayaram, 2008; Bradley, 2012b).…”
Section: Introductionmentioning
confidence: 96%
“…This approach is referred to as the approximate method versus the exact in which all causal events in the disaggregation analysis are considered to generate the target spectrum 46 . The correlation coefficients for the H‐H components of Sa’ s are defined based on Baker and Jayaram, 92 while the correlations between V‐V and V‐H components of Sa’ s are adopted from Kohrangi et al 43 . An upper bound limit equal to 5 is imposed to the scaling factors, a condition which is violated only for high IM levels where a good match could not be achieved by restricting scaling factors to 5, and in few cases factors up to 9 were utilized.…”
Section: Hazard Intensity Measures and Ground Motionsmentioning
confidence: 99%
“…Incorporating the vertical component in the standard CS approach of Lin et al, 46 where a scalar IM is employed as the conditioning variable, is an exercise that requires accounting for the vertical spectral acceleration ordinates in the joint lognormal model assumed therein. Given the availability of correlation coefficients between V spectral ordinates, as well as those between V and H ones, 43 we employed the algorithm of Jayaram et al 5,47 to match the resulting conditional horizontal and vertical target spectra, thus enabling the selection of ground motion records where all three components are compatible with the site hazard. 44,45 Herein, to avoid repeating the formulations of the standard CS record selection, we decide to omit them and refer the interested reader to, 46 as needed.…”
Section: Conditional Spectra Based On Scalar Conditioning Imsmentioning
confidence: 99%
See 1 more Smart Citation